PD-1, PD-L1, and PD-L2 Gene Expression and Tumor Infiltrating Lymphocytes in Canine Melanoma. Issue 4 (July 2021) - Stevenson, Valentina B.; Perry, Samantha N.; Todd, Michelle; Huckle, William R.; LeRoith, Tanya
Melanoma in humans and dogs is considered highly immunogenic; however, the function of tumor-infiltrating lymphocytes (TILs) is often suppressed in the tumor microenvironment. In humans, current immunotherapies target checkpoint molecules (such as PD-L1, expressed by tumor cells), inhibiting their suppressive effect over TILs. The role of PD-L2, an alternative PD-1 ligand also overexpressed in malignant tumors and in patients with anti-PD-L1 resistance, remains poorly understood. In the current study, we evaluated the expression of checkpoint molecule mRNAs in canine melanoma and TILs. Analysis of checkpoint molecule gene expression was performed by RT-qPCR (real-time quantitative polymerase chain reaction) using total RNA isolated from formalin-fixed and paraffin-embedded melanomas ( n = 22) and melanocytomas ( n = 9) from the Virginia Tech Animal Laboratory Services archives. Analysis of checkpoint molecule expression revealed significantly higher levels of PDCD1 ( PD-1 ) and CD274 ( PD-L1 ) mRNAs and an upward trend in PDCD1LG2 ( PD-L2 ) mRNA in melanomas relative to melanocytomas. Immunohistochemistry revealed markedly increased numbers of CD3 + T cells in the highest PD-1 -expressing subgroup of melanomas compared to the lowest PD-1 expressors, whereas densities of IBA1 + cells (macrophages) were similar in both groups. CD79a + cell numbers were low for both groups. As in human melanoma, overexpression of the PD-1/PD-L1/PD-L2 axis is a common feature of canine melanoma. High expression of PD-1 and PD-L1 correlates with increased numbers of CD3 + cells. Additionally, the high level of IBA1 + cells in melanomas with low PD-1 expression and low CD3 + cells levels suggest that the expression of checkpoint molecules is modulated by interactions between T cells and cancer cells rather than histiocytes.